PREVALENCE AND STRUCTURE OF DISEASES TONGUE IN YOUNG PATIENTS - Yeroshenko, G.А.; Semenova, А.K.; Gasiuk, N.V. (World of Medicine and Biology, 2013)
To date, there is no doubt the relationship chain pathogenesis of diseases of the oral mucosa and periodontal fabric of presence and flow in the patient's somatic pathology. The structure of language disorders in persons surveyed contingent prevailed descvamatic glossitis. There is no clear link with the state of oral health status and periodontal tissues, and there is a clear clinical association with diseases of gastrointestinal tract.
Keywords: tongue; digestive canal; atrophy; hyperplasia; structure